Atomic structure and dynamics of metal dopant pairs in graphene. - He, Z; He, K; Robertson, A; Kirkland, A; Kim, D; Ihm, J; Yoon, E; Lee, G; Warner, J (American Chemical Society, 2014)
We present an atomic resolution structural study of covalently bonded dopant pairs in the lattice of monolayer graphene. Two iron (Fe) metal atoms that are covalently bonded within the graphene lattice are observed and their interaction with each other is investigated. The two metal atom dopants can form small paired clusters of varied geometry within graphene vacancy defects. The two Fe atoms are created within a 10 nm diameter predefined location in graphene by manipulating a focused electron beam (80 kV) on the surface of graphene containing an intentionally deposited Fe precursor reservoir. Aberration-corrected transmission electron microscopy at 80 kV has been used to investigate the atomic structure and real time dynamics of Fe dimers embedded in graphene vacancies. Four different stable structures have been observed; two variants of an Fe dimer in a graphene trivacancy, an Fe dimer embedded in two adjacent monovacancies and an Fe dimer trapped by a quadvacancy. According to spin-sensitive DFT calculations, these dimer structures all possess magnetic moments of either 2.00 or 4.00 μB. The dimer structures were found to evolve from an initial single Fe atom dopant trapped in a graphene vacancy.